A perenização dos registros criminais dos inocentados pela justiça: uma abordagem à luz dos direitos fundamentais - Gomes, José Geraldo (2011)
We seek to meet the constitutional hermeneutics, specifically regarding the rules relating to fundamental rights, with the aim of identifying possible violation of personal rights, especially human dignity, on the perpetuation of the criminal records of individuals who despite being indicted in the police investigation or subject to criminal proceedings, prove your innocence before the courts. Necessary to interpret and investigate the scope of the rules contained in Articles 1, III and IV, 5, III, X and XIII of the Constitution, 93 CP, 20 and 748 of the CPP, as well as Article 202 of the LEP to finally understand the (un) necessary to the perpetuation of the criminal in the face of proven innocence. Sees itself, a priori, an offense against the fundamental rights of human dignity, with respect to art. 5, III, CF, since no one [...] “shall be subjected to degrading treatment”. The protection item X image, intimacy and privacy of the individual. Art. 1, III states as the foundations of the Federative Republic of Brazil, among others, “the dignity of the human person” and section IV, “the social values of work”. In the event of injury to identify fundamental rights, investigate the position of the courts of their ancestors on the matter, trying to find legally, the possibility of exclusion from registration data of the innocent, as a way to repair the damage by the government at the expense of citizens. We argue the existence and validity of the fundamental Right to oblivion, as legitimacy to rule out the cast acquitted of criminal social control bodies of the state. We use the dialectical method, grounded in research literature, loose collection of publications, legal articles, books, monographs and dissertations on related topics, polls and votes of the Supreme Court case Law and Supreme Court. The study is structured in four chapters. The first, on fundamental rights. The second, on the right to investigate and punish the state, with its legal limitations. The third, on the fundamental right to oblivion. The fourth on the perpetuation of criminal records of unconvicted justice.